Pengaruh Knowledge Sharing dan Knowledge Acquisition Factor Terhadap Niat Penggunaan E-Learning Sebagai Media Pembelajaran Menggunakan Metode PLS-SEM - Adya Salwa Dyani; Ken Ditha Tania; Ari Wedhasmara; Allsela Meiriza (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
E-learning at Sriwijaya University is an electronic learning system used to provide education and training to students through an online platform. In its use, e-learning provides students with the flexibility to study independently, according to their schedule and needs. This study provides an important insight into the factors affecting students’ intention to use e-learning as a learning medium, especially in the context of the aftermath of COVID-19. The results of this study can be used by colleges and educational institutions to increase the effectiveness of e-learning in online learning. This study aims to investigate the influence of knowledge sharing and knowledge acquisition factors on the intention of using e-learning as a learning medium in the academic environment after COVID-19. Factors studied include Subjective Norms (SN), Self-Efficacy (SE), Knowledge Sharing (KS), Knowledge Acquisition (KA), Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Satisfaction (SAT), and Adherence (SAT). This study used the Expectation Confirmation Model (ECM) research model. Data were collected through a survey of active students at Sriwijaya University, with a sample of 500 respondents. Data analysis uses Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Research results show that important Knowledge Management factors such as Knowledge Sharing (KS) and Knowledge Acquisition (KA) have a positive effect on reviewing the intention of using e-learning as a learning medium. Other factors also have a positive and significant effect on e-learning intentions